Enhancing Financial Inclusion and Community-Based Economic Resilience through Fintech Adoption among SMEs in Nigeria - Ali Nuhu Abubakar; Maryam Rabi’u Zakariyya; Tijjani Lawan Ibrahim; Hafsat Garba Usman (Help: Journal of Community Service, 2026)
Financial inclusion remains a significant challenge for many Small and Medium Enterprises (SMEs) in Nigeria, particularly regarding access to formal financial services, digital financial literacy, and sustainable business financing. This community service program aimed to enhance financial inclusion and strengthen community-based economic resilience through the adoption of financial technology (Fintech) among SMEs. The program employed an Asset-Based Community Development (ABCD) approach involving 50 SME owners from various business sectors. Activities included needs assessment, financial literacy training, Fintech workshops, hands-on demonstrations, individualized mentoring, and program evaluation. Quantitative data were collected through pre-test and post-test assessments and participant surveys, while qualitative data were obtained through interviews and focus group discussions. The results revealed substantial improvements in financial literacy and Fintech awareness, with average knowledge scores increasing from 52.1% to 83.9%. A total of 94% of participants successfully adopted at least one Fintech service, including digital payment platforms, mobile banking, e-wallets, and online financing applications. Furthermore, the program strengthened community-based economic resilience by fostering collaboration among SMEs, enhancing business networks, increasing access to financial information, and improving participants’ ability to respond to economic challenges. The discussion highlighted that the integration of financial literacy, Fintech adoption, and collaborative digital empowerment contributed not only to financial inclusion but also to the development of social capital and community resilience. The program demonstrates that community-based digital financial empowerment can serve as an effective strategy for promoting inclusive economic development and strengthening the sustainability of SMEs in developing economies.